Metode Dakwah Ustadz Fadzlan Garamatan Pada Masyarakat Nuu Waar (Papua) - Muhamad Afdoli Ramadoni, Edi Amin, WG Pramita Ratnasari (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2022)
The contribution of a preacher is very important in developing Islamic teachings. In his activities, the da'i struggles to straighten out his creed and uphold the Amar Ma'rf Nahi Munkar. Ustadz Fadzlan Garamatan is a preacher who is famous for his da'wah method in the interior of Papua. Through a unique concept and approach, he teaches proper and correct bathing procedures using good and correct water and soap (thâharah) and conveys the values of Islamic da'wah. The method used in this research is descriptive analysis method through a qualitative approach. This method is in the form of direct observation and interviews with Ustadz Fadzlan Garamatan. The findings of this study indicate that the da'wah method carried out by Ustadz Fadzlan Garamatan is in accordance with the first, the bi al-Hikmah method through the form of thâharah the practice of bathing with water and soap. Second, the method of bi al-Mau'izah al-Hasanah uses da'wah bi al-Lisan, bi al-'Amal and bi-al_Qolam. Third, the bi al-Mujlah bi-al-Lati Hiya Ahsan method provides advice and builds dialogue with religious leaders, traditional leaders, and tribal leaders as well as coaching the converts. So that the message of da'wah conveyed can change mad to continue working on amar ma'rūf nahy munkar, and the peak of the creation of good morals.